Investigação de surto de tuberculose em clínica de hemodiálise: uma ação intersetorial de saúde pública - Maíce Vieira Marinho Henriques; Nayane Silva Almeida; Maria Luiza Vitoraci de Souza; Leticia Barletta; Murilo Soares Costa (Health and Biosciences, 2026)
Tuberculosis is an infectious disease whose transmission occurs through the air and the time of exposure to the pathogen. It presents itself as a major challenge to global public health and can be potentiated in hemodialysis units where patients with weakened immunity due to immunosuppression are found. Intersectorality, in turn, is the integration of services with the purpose of putting public policies into practice. The objective of the study was to describe the intersectoral investigation conducted in response to the identification of tuberculosis cases in a hemodialysis clinic attached to a public hospital located in the city of São Mateus, Espírito Santo, Brazil. Some cases of tuberculosis were identified and, due to this occurrence, an intersectoral task force was organized to identify infected patients, control the epidemic, through partnership with health units and epidemiological surveillance services of the municipalities of reference, and treat the disease. The experience described in this report on tuberculosis reinforces how much intersectoral action is decisive for the effective confrontation of complex situations in public health, among its different levels of care. The integrated action of this experience showed how it is possible to work with the health network in favor of comprehensive care for users who use public health services. In view of this, intersectorality can contribute to the promotion of measures for the control and treatment of tuberculosis.